2015
DOI: 10.1111/andr.12000
|View full text |Cite
|
Sign up to set email alerts
|

Sperm retrieval outcomes with microdissection testicular sperm extraction (micro-TESE) in men with cryptozoospermia

Abstract: SUMMARYSeveral studies support of the use of testicular rather than ejaculated spermatozoa for intracytoplasmic sperm injection (ICSI) in couples with virtual azoospermia or cryptozoospermia, although this approach remains controversial. We sought to evaluate sperm retrieval outcomes with microdissection testicular sperm extraction (micro-TESE) in men with cryptozoospermia. We conducted a retrospective study of 24 consecutive micro-TESEs in men with cryptozoospermia. We also evaluated the outcomes of seven con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 24 publications
4
33
0
Order By: Relevance
“…Nagy et al (1995) and Aboulghar et al (1997) reported that the fertilization and pregnancy rates by testicular spermatozoa were significantly lower than those of ejaculated and epididymal spermatozoa in non-obstructive azoospermia (10, 15). The sperm extraction proportion from testicular and epididymis in our study was similar but fertility outcomes in PESA sub-group was significantly better than outcomes of TESE sub-group, similar to the results of Alrabeeah et al (16). In contrast to our study results, Some researchers believe that the fertilization rate of testicular extracted spermatozoa from non-obstructive azoospermic men is comparable to ejaculated spermatozoa in men with unexplained fertility and also stated that the fertilization rate of severe oligospermia or cryptozoospermia is similar to that of testicular spermatozoa source (15, 18, 19).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nagy et al (1995) and Aboulghar et al (1997) reported that the fertilization and pregnancy rates by testicular spermatozoa were significantly lower than those of ejaculated and epididymal spermatozoa in non-obstructive azoospermia (10, 15). The sperm extraction proportion from testicular and epididymis in our study was similar but fertility outcomes in PESA sub-group was significantly better than outcomes of TESE sub-group, similar to the results of Alrabeeah et al (16). In contrast to our study results, Some researchers believe that the fertilization rate of testicular extracted spermatozoa from non-obstructive azoospermic men is comparable to ejaculated spermatozoa in men with unexplained fertility and also stated that the fertilization rate of severe oligospermia or cryptozoospermia is similar to that of testicular spermatozoa source (15, 18, 19).…”
Section: Discussionsupporting
confidence: 91%
“…In order to avoid the cancellation of ICSI in these cases, most infertility centers provide an alternative surgically sperm extraction (PESA or TESE) (10) synchronous to oocyte retrieval (16); however, there is a debate about outcomes of ejaculated sperm and extracted sperm in literature. Therefore, we conducted a prospective cohort study to highlight outcome differences in these two methods of sperm retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a successful mini‐incision micro‐TESE, 2–5 additional biopsies are harvested from the superficial tissue to ensure that sufficient numbers of spermatozoa will be available for ICSI. We established that the intra‐operative identification of ≥5 spermatozoa was a minimum number based on our recent observations (Alrabeeah et al ., ). We sub‐categorized the micro‐TESE procedures into two groups (1‐mini‐incision micro‐TESE and 2‐standard unilateral or bilateral microTESE) based on the extent of testicular dissection.…”
Section: Methodsmentioning
confidence: 97%
“…As part of the procedure, most centers perform an immediate (intra‐operative) microscopic assessment of the extracted testicular tissue. This will help guide the surgeon on the need to continue extracting tissue in the ipsilateral and/or contra‐lateral testis or terminate the procedure (Tsujimura et al ., ; Turunc et al ., ; Ramasamy et al ., , ; Alrabeeah et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation